ANALISIS PENYEBAB PUTUS SEKOLAH JENJANG PENDIDIKAN SMP DI DESA AUR SAMPUK KECAMATAN SENGAH TEMILA - FernandoAm, Ferdi Putra; Bahari, Yohanes; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is entitled, "Factors Analysis of the Causes of School Drop Outs in the Secondary School Education Level in Aur Sampuk Village, Sengah Temila District, Landak Regency". A common problem in this study is "Factors Causing School Drop Outs from inside and outside?" The general objective in this research is to find out "Factors Causing School Drop Outs from inside and outside". The approach used in this research is a qualitative approach with descriptive methods. Data collection techniques used were observation techniques, interview guides, and documentation. The informants in this study were school dropouts and parents of school dropouts. The results showed that, factors causing children to drop out of school originating from within the child such as the desires and interests of children not to go to school and those originating from outside the child such as the economic ability of parents, awareness of the importance of education, and the child's social environment. On the factors that originate from within the child the child stops going to school because of his own desire. While factors originating from outside the child, such as the economic ability of parents, realize the importance of education and the child's social environment.Keywords: Children Inside, Out of Children, School Drop OutsÂ